Palynological study of Bornean Nepenthes (Nepenthaceae) - H. Adam, Jumaat; C. C., Wilcock (Universiti Putra Malaysia Press, 1999)
Palynological study shows that the mean pollen tetrad size of 27 Bornean Nepenthes species ranges from 27Um to 38.9 Um, thus falling into the small and medium-sized grain class. Aperture type, exine sculpturing, pollen unit and shape are homogeneous among Bornean species and thus not taxonomically useful at the specific and sectional level. The mean pollen tetrad size revealed that the species under investigation can be divided into three groups: Group 1: 27 Um, Group 11:28.5-34.7 Um, and Group IIl:37.2-38.9 Um.